Pelaksanaan Pembelajaran Matematika Berbasis Kurikulum Merdeka: Studi Kasus di MAN 2 Kota Padang - Izatul Hasanah; Nita Putri Utami (Pentagon : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2025)
This study aims to describe the implementation of mathematics learning based on the Independent Curriculum at MAN 2 Kota Padang, focusing on teacher-student interaction and the overall effectiveness of the learning process. The observation covered three main phases: introductory, core, and closing activities. A phenomenological approach was applied using both qualitative and quantitative methods. Data were collected through direct classroom observations, interviews with mathematics teachers and students, as well as analysis of teaching documents. Instruments included Yes-No questionnaires, interview guidelines, and documentation review. The findings indicate that the learning process aligns with the principles of the Independent Curriculum, as reflected in the varied instructional strategies, active student engagement, and teacher readiness in applying learning modules. The effectiveness of learning was very high, with 95.21% in grade X and 92.99% in grade XI. Challenges included limited time and lack of participation from some students. Overall, the learning process fostered an active, meaningful environment that supports character development.